Consumer motivations for engaging with corporate social responsibility on social media - Aguirre, Claudia; Ruiz de Maya, Salvador; Palazón Vidal, Mariola; Rodríguez, Augusto (Spanish journal of marketing-ESIC, 2023)
Purpose This study aims to analyze consumer motivations to share information about corporate social responsibility (CSR) activities through electronic word of mouth. It examines the roles of self-enhancement, identity signaling and social bonding as antecedents of consumers’ CSR engagement on social media. Design/methodology/approach A quantitative approach is used with a single-factor between-subjects experimental design in which the presence vs absence of CSR information on a company website is manipulated. The hypotheses are tested through structural equation modeling. Findings Results show that after viewing the company’s CSR message on its website, consumers who generated more CSR associations were more motivated to engage with the CSR information to satisfy fundamental personality traits (need for self-enhancement) and social relationship motivations (social bonding), which increased their intention to share the information. Research limitations/implications This study is restricted to CSR information on websites. Further research should consider what happens if such information is shared on social media, as consumers are more likely to spread CSR messages when they are shared by other public social network sites. Practical implications The study highlights the relevance of including CSR information on websites and offers insights into the importance of considering consumers in disseminating CSR information. Consumers share information when they have personal motivation for doing so. Social implications This study put the focus on the role of consumers in the diffusion of corporate information. Originality/value The results show the importance of personal motivations such as self-enhancement and social bonding in sharing CSR information on social media. Propósito El estudio analiza las motivaciones que tiene el consumidor para compartir información sobre acciones de responsabilidad social corporativa (RSC) a través de boca oído electrónico (eWOM). En particular, las motivaciones de mejora del auto-concepto, necesidad de mostrar una identidad deseada y la vinculación social. Metodología Se utiliza un diseño experimental entre sujetos donde se manipuló la presencia vs ausencia de información sobre la RSC de la empresa. Las hipótesis se contrastaron mediante un modelo de ecuaciones estructurales. Resultados Los resultados muestran que los consumidores con más asociaciones de RSC comparten más la información de RSC motivados por satisfacer la mejora del auto-concepto y vinculación social. Implicaciones prácticas El estudio destaca la importancia de generar contenido de RSC en el sitio web de la empresa, y la importancia de los consumidores en la difusión de información de dicha información. Limitaciones El estudio está restringido a la presencia de información de RSC en el sitio web de la empresa. Sería interesante evaluar lo que sucede si dicha información se comparte en redes sociales, en la medida en que los consumidores tienen mayor tendencia a compartir la información procedente de redes sociales. Originalidad Los resultados muestran la importancia de las motivaciones personales como la mejora del auto-concepto y la vinculación social a la hora compartir información de RSC en las redes sociales. 目的 本研究分析了消费者通过电子口碑分享企业社会责任（CSR）活动信息的动机。它研究了自我提升、身份信号和社会联系作为消费者在社交媒体上参与企业社会责任的前因的作用。 方法 采用单因素主体间实验设计的定量方法, 对公司网站上企业社会责任信息的存在与否进行操纵。假设通过使用R软件包lavaan的结构方程模型进行检验。 研究结果 结果显示, 在观看公司网站上的企业社会责任信息后, 产生更多企业社会责任联想的消费者更有动力参与到企业社会责任信息中, 以满足基本的人格特征（自我提升的需要）和社会关系动机（社会纽带）, 这增加了他们分享信息的意向。 实践意义 该研究强调了将企业社会责任信息纳入网站的相关性, 并对在传播企业社会责任信息时考虑消费者的重要性提出了见解。消费者在有个人动机的情况下会分享信息。 研究局限性 本研究仅限于网站上的企业社会责任信息。进一步的研究应该考虑到社交媒体, 因为当消费者在其他公共社交网站上分享企业社会责任信息时, 他们更有可能进行传播。 原创性 研究结果表明, 在社交媒体上分享企业社会责任信息时, 自我提升和社会联系等个人动机的重要性。